Enhancing Rumor Riding protocol in P2P network with Cryptographic puzzle through challenge question method. (January 2018) - Christo, Mary Subaja; Meenakshi, S.
Abstract: This research seeks is to investigate the Peer to Peer network topology and its custom behavior. The habitual effect of Peer to Peer network includes considering all the connected nodes as peers and these peers head-on with other peers to effectuate the tasks assigned to each one of them. The entire embrace of this network topology clings on to the heterogeneous sphere. Due to its comprehensive network topology and penchant features, the network is vulnerable to many castigating attacks. Furthermore, the possession attributed to the security traits of the network is comparatively tiny. Thus, this network topology is subjected to copious attacks. Rumor Riding (RR) is an anonymous and non-path based protocol. In this protocol, three nodes (including the Initiator, Intermediate, and Responder) are involved in sharing the information or searching the file. In some cases, the named three nodes may act as attackers leading to initiator attacks, intermediate attacks and responder attacks. The reason behind the argument is that RR protocol is based on an anonymous method that tends to hide the information from source to destination without authentication. Hence, the network performance gradually becomes ineffective. The main intent of this paper is to explore the ways and means to prevent all the stated onslaughts. To achieve this, we have developed an attack prevention protocol. The protocol involves the Reliable Rumor Riding Protocol in P2P Network through the Cryptographic Puzzle attributed to the Challenge Question Method. Furthermore, we have augmented the performance and measured. Hence, in this quintessential way, the network operation is proved to be secured and authenticated.